2021
DOI: 10.3390/curroncol28030173
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Distress in Adult Patients Awaiting Cancer Surgery during the COVID-19 Pandemic

Abstract: Cancer causes substantial emotional and psychosocial distress, which may be exacerbated by delays in treatment. The COVID-19 pandemic has resulted in increased wait times for many patients with cancer. In this study, the psychosocial distress associated with waiting for cancer surgery during the pandemic was investigated. This cross-sectional, convergent mixed-methods study included patients with lower priority disease during the first wave of COVID-19 at an academic, tertiary care hospital in eastern Canada. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…Nonetheless, other studies have recently focused on patients affected by other pathological conditions. The analysis conducted by Forner and colleagues underlined that delays in surgery for cancer patients due to the pandemic resulted in extensive psychosocial distress, and found that patients could mitigate these effects through various coping mechanisms and improved communication with their healthcare teams [15]. Furthermore, the COVID-19 lockdown significantly and negatively impacted younger people with multiple sclerosis (MS), in particular in those with progressive types of MS and psychological symptoms [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other studies have recently focused on patients affected by other pathological conditions. The analysis conducted by Forner and colleagues underlined that delays in surgery for cancer patients due to the pandemic resulted in extensive psychosocial distress, and found that patients could mitigate these effects through various coping mechanisms and improved communication with their healthcare teams [15]. Furthermore, the COVID-19 lockdown significantly and negatively impacted younger people with multiple sclerosis (MS), in particular in those with progressive types of MS and psychological symptoms [16].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment protocols for cancer patients have changed, and healthcare provisions have decreased [ 4 , 5 ]. The delay in the diagnosis and treatment of the disease has caused psychological pain among cancer patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with cancer, it has impacted both treatment and recovery trajectories. 1 , 2 Patients with hematologic malignancies undergoing hematopoietic stem cell transplantation (HSCT) are especially vulnerable to care changes imposed by the pandemic due to factors associated with HSCT, including the intensive treatment with a prolonged hospitalization, high burden of physical symptoms due to potential toxic side effects, and quality of life (QOL) challenges in recovery. 3 , 4 , 5 , 6 Outside the hospital, HSCT patients grapple with weeks of social isolation and quarantine requirements from a compromised immune system, contributing to distress and QOL impairments in this population.…”
Section: Introductionmentioning
confidence: 99%